Les saisies et perquisitions en matière fiscale : le contribuable n'est plus maître de sa maison - Lareau, André (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
In order to remind those taxpayers who forgot to pay tax on some of their income, the search and seizure procedures have been put back to work in the last few years. This article does not question the validity of the principle itself. However, it analyzes the frequent problems that arise with respect with the seizure, whether they be related to an overzealous civil servant or to the agreement given by the judge. It also finds that more and more judicial procedures are available to the taxpayers to help them in their fight against the taxman.